2016
DOI: 10.1038/srep31968
|View full text |Cite
|
Sign up to set email alerts
|

Strains of the Propionibacterium acnes type III lineage are associated with the skin condition progressive macular hypomelanosis

Abstract: Progressive macular hypomelanosis (PMH) is a common skin disorder that causes hypopigmentation in a variety of skin types. Although the underlying aetiology of this condition is unclear, there is circumstantial evidence that links the skin bacterium Propionibacterium acnes to the condition. We now describe the first detailed population genetic analysis of P. acnes isolates recovered from paired lesional and non-lesional skin of PMH patients. Our results demonstrate a strong statistical association between stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…In contrast, the present study showed a striking predominance of subtype III in PMH lesional samples from the lower, middle, and upper back, and abdomen. This corroborates the previous finding of a unique, unidentified P. acnes type in PMH patients [22], and the recent report that type III strains were cultured from lesions of 14 of 34 PMH patients [24]. …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, the present study showed a striking predominance of subtype III in PMH lesional samples from the lower, middle, and upper back, and abdomen. This corroborates the previous finding of a unique, unidentified P. acnes type in PMH patients [22], and the recent report that type III strains were cultured from lesions of 14 of 34 PMH patients [24]. …”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found a highly significant increase in P. acnes numbers in PMH lesions [11, 24]. In accordance, we could also confirm that P. acnes is more abundant in lesions compared to nonlesional skin: a semiquantitative analysis revealed that all PMH samples from patients had a higher colony-forming unit count as compared to adjacent nonlesional skin (data not shown).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations